Pendampingan Masyarakat dalam Pengembangan Potensi Wisata - Hajril, Muhammad; M. Billah Jaya Nusantara; Rauf, Abdur; Moh Ngubaidillah; Nurlia, Siti; Abdullah, khairunnisa (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2024)
This program aims to provide the community with an understanding of tourism management and direct assistance through the creation of directional signs and entrance gateways for the tourism site. The implementation of this program adopts the ABCD method and begins with interviews and observations. The management assistance activities begin with the village apparatus and then coordinate with the community managing Sumber Bening. After coordination, planning is carried out, including the creation of directional signs and entrance gateways. The results of this program include the creation of directional signs, gateways, and their installation. The sustainable impact of this program includes directional signs and gateways that can serve as guidance for visitors who want to visit the tourism. Furthermore, this program also collaborates with the hamlet authorities responsible for Sumber Bening, providing them with an understanding of tourism management to facilitate their future management efforts.